2022
DOI: 10.3390/ma15031200
|View full text |Cite
|
Sign up to set email alerts
|

Spectrometric Analysis of the Wear from Metallic and Ceramic Dental Implants following Insertion: An In Vitro Study

Abstract: Titanium wear is a growing area of interest within dental implantology. This study aimed to investigate titanium and zirconium wear from dental implants at the time of insertion using X-ray-fluorescence spectrometry (XRF) and an in vitro protocol utilizing artificial bovine bone plates. Five groups were analyzed using XRF-spectrometry: groups 1–4 (titanium implants) and group 5 (zirconia implants). The implants were inserted into two bone blocks held together by a vice. The blocks were separated, and the inser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…It was suspected that metallic ions could be generated before the corrosion of the metallic implant, starting from the surgical insertion, due to abrasion of the implant. An investigation on simulated bone materials, consisting of polyurethane foam with different densities found that no particles were released during insertion [154], while another investigation that used bovine bone blocks detected Ti after insertion [155]. Regardless, metallic debris can be released over time into the surrounding tissue and it appears that these particles are contributing to the inflammatory response [156][157][158].…”
Section: Peri-implantitis As Related To Metallic Implant Biomaterialsmentioning
confidence: 99%
“…It was suspected that metallic ions could be generated before the corrosion of the metallic implant, starting from the surgical insertion, due to abrasion of the implant. An investigation on simulated bone materials, consisting of polyurethane foam with different densities found that no particles were released during insertion [154], while another investigation that used bovine bone blocks detected Ti after insertion [155]. Regardless, metallic debris can be released over time into the surrounding tissue and it appears that these particles are contributing to the inflammatory response [156][157][158].…”
Section: Peri-implantitis As Related To Metallic Implant Biomaterialsmentioning
confidence: 99%
“…Teeth have a limited capacity for self-regeneration; consequently, it is necessary to replace the damaged bone part with a graft that has high biocompatibility, osteoinductivity, osteoconductivity, osteointegrativity, and suitable mechanical properties [2,3]. Replacing missing teeth with a dental implant is an operation with a high success rate, good predictability, versatility, and fewer complications [4,5].…”
Section: Introductionmentioning
confidence: 99%